DYNAMICAL PRODUCTION FUNCTIONS IN ECONOMETRIC ANALYSIS - В. О. Янковий (Ринкова економіка: сучасна теорія і практика управління, 2018)
The article deals with theoretical and applied problems of modeling the dynamics of technical and economic indicators of modern market and production systems on the basis of two-factor production functions. The analytic possibilities of the Cobb-Douglas functions, CES functions are discussed. Practical aspects of application of the indicated production functions are illustrated by the example of modeling of economic activity of the machine-building industry of Ukraine and other commodity producers.